Antiviral Potency of Glycyrrhizin and Glycyrrhetic Acid against SARS-CoV-2 Infection of the Non-Structural Protein 3, Main Protease, and Spike Glycoprotein Receptors - Mutiah, Roihatul; Indrawijaya, Yen Yen Ari; Suryadinata, Arief; Adyuta, Nandana (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR), 2025)
The efforts to develop antiviral for Covid-19 are still being conducted. One of them is the exploration of the antiviral potency of the compounds found in licorice namely glycyrrhizin and glycyrrhetic acid. They are used and developed further using molecular docking. The research aims to predict the antiviral potency of glycyrrhizin and glycyrrhetic acid against SARS-CoV 2 infection. The researcher employs SwissADME Tool in testing Lipinski’s rule of five fulfillments to predict their physicochemistry. To get an optimum result, the researcher prepares the compounds and receptors. The receptors are validated with RMSD value <2Å, namely Non-Structural Protein 3 (6VXS), Main Protease (6W63), and Spike Glycoprotein (6VSB). The result shows that glycyrrhetic acid fulfills Lipinski’s rule of five, in contrast with glycyrrhizin. Both compounds have good energy affinity and inhibition constant with the best value -13.6 kcal/mol and 0.000104 µM on the receptor 6W63. The interaction between Glycyrrhizin and amino acid residue is found in the interaction with the 6VXS, 6W63, and 6VSB receptors. Meanwhile, glycyrrhetic acid compound only interacts with the receptor 6VXS. The interaction between glycyrrhizin and glycyrrhetic acid and its target protein has antiviral activity potency against SARS-CoV 2 infection.